2022
DOI: 10.21203/rs.3.rs-1913200/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of publication bias for 12 clinical trials of molnupiravir to treat SARS-CoV-2 infection in 13,694 patients

Abstract: Introduction: During the COVID-19 pandemic, Merck Sharp and Dohme (MSD) acquired the global licensing rights for molnupiravir. MSD allowed Indian manufacturers to produce the drug under voluntary license. Indian companies conducted local clinical trials to evaluate the efficacy and safety of molnupiravir. Methods Searches of the Clinical Trials Registry-India (CTRI) were conducted to find registered trials of molnupiravir in India. Subsequent investigations were performed to assess which clinical trials had … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Concern has been raised regarding the lack of public sharing or formal publication of the findings of these three trials, along with nine others, all of which were conducted in India. 23 The reviews found that molnupiravir probably reduces: hospitalisation (odds ratio 0•54; 95% CI: 0•30 to 0•90; n=5 trials); and, time to symptom resolution (-3•3 days; 95% CI: -4•8 days to -1•6 days; n=3 trials). The WHO therefore advises that molnupiravir may be of benefit in outpatients with mild-moderate COVID-19 at the highest risk of an adverse outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concern has been raised regarding the lack of public sharing or formal publication of the findings of these three trials, along with nine others, all of which were conducted in India. 23 The reviews found that molnupiravir probably reduces: hospitalisation (odds ratio 0•54; 95% CI: 0•30 to 0•90; n=5 trials); and, time to symptom resolution (-3•3 days; 95% CI: -4•8 days to -1•6 days; n=3 trials). The WHO therefore advises that molnupiravir may be of benefit in outpatients with mild-moderate COVID-19 at the highest risk of an adverse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The observed median (IQR) time-to-first-recovery from randomisation was 9 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) 2). Subgroup analysis demonstrated that this benefit was consistent across all studied groups.…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Concern has been raised about the lack of public sharing or formal publication of the findings of these three trials, along with those of nine others, all of which were done in India. 21 The reviews 19,20 reported that molnupiravir probably reduces hospitalisation (odds ratio 0•54 [95% CI 0•30 to 0•90]; based on five trials) and time to symptom resolution (-3•3 days [-4•8 days to -1•6 days]; based on three trials). WHO therefore advises that molnupiravir might benefit outpatients with mild-to-moderate COVID-19 at the highest risk of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%